2002
DOI: 10.1016/s0378-1097(02)01070-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific identification and molecular typing analysis of Lactobacillus johnsonii by using PCR-based methods and pulsed-field gel electrophoresis

Abstract: A fast and reliable Multiplex-PCR assay was established to identify the species Lactobacillus johnsonii. Two opposing rRNA genetargeted primers have been designed for this specific PCR detection. Specificity was verified with DNA samples isolated from different lactic acid bacteria. Out of 47 Lactobacillus strains isolated from different environments, 16 were identified as L. johnsonii by PCR. The same set of strains was investigated with five alternative molecular typing methods: enterobacterial repetitive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 22 publications
2
60
0
5
Order By: Relevance
“…Strains sharing the same pattern came from the same sample, leading us to think that they represented the same strain isolated several times. Ferrero et al (1996), Zapparoli et al (1998) and Ventura & Zink (2002) reported discriminatory, clear and reproducible RFLP-PFGE patterns in various Lactobacillus species, which allowed its use for typing studies. Our results agree with their observations.…”
Section: Numerical Analysis Of Rflp-pfge Patternsmentioning
confidence: 97%
“…Strains sharing the same pattern came from the same sample, leading us to think that they represented the same strain isolated several times. Ferrero et al (1996), Zapparoli et al (1998) and Ventura & Zink (2002) reported discriminatory, clear and reproducible RFLP-PFGE patterns in various Lactobacillus species, which allowed its use for typing studies. Our results agree with their observations.…”
Section: Numerical Analysis Of Rflp-pfge Patternsmentioning
confidence: 97%
“…longum DJO10A) followed by a second PCR amplification with primers specific for 16S rRNA genes found in all members of the genus Bifidobacterium: LM3 (5 0 -CG GGTGCTIcCCCACTTTCATG-3 0 ) and LM26 (5 0 -GAT TCTGGCTCAGGATGAACG-3 0 ) (the targeted amplicon corresponds to bases 12 to 1400 of the 16S rRNA gene of B. longum subsp. longum DJO10A) according to the PCR protocols described earlier (Kaufmann et al, 1997;Ventura & Zink, 2002).…”
Section: Construction Of 16s Rrna Gene Librariesmentioning
confidence: 99%
“…ERIC-PCR was performed using the forward primer 5'-atg taa gct cct ggg gat tca c-3' and reverse primer 5'-aag taa gtg act ggg gtg agc g-3' (Ventura & Zink 2002). Each 50 µl reaction mixture contained 5 µl 10× reaction buffer (Roche), 200 µM of each deoxynucleoside triphosphates (Invitrogen), 25 pmol of each primer (Invitrogen), 2 U Taq polymerase (Roche) and 20 ng of the respective DNA template.…”
Section: Fishmentioning
confidence: 99%